Solvent extraction of peanut oil: optimization using response surface methodology - Abu Samah, Norafikah (2019)
In the production of peanut oil, plenty of extraction method could be used to extract the seed oil. This study focused on seed oil extraction by conventional method and optimized by response surface methodology. The study was performed by using different parameters as to find the optimum condition for the extraction process. The process parameters were further optimized by statistical approach using historical data design of response surface method (RSM) to find the optimum parameters for the highest oil yield.